Innovation in islamic education teaching methods: improving teacher effectiveness and creativity at MTs Labanan Makmur - Reka Oktavia; Arifin Siregar; Dina Mardiana (ARKA INSTITUTE, 2026)
Innovations in Islamic Education teaching methods at MTs Labanan Makmur aim to improve the effectiveness and creativity of teachers in teaching. This study examines various innovative strategies applied by teachers to address dynamic learning challenges and diverse student needs. The methods developed include the use of technology, interactive approaches, and the contextual and creative integration of Islamic values. The results show that innovative PAI teaching methods at MTs Labanan Makmur can improve teacher effectiveness and creativity, which in turn increases student motivation and the quality of teacher-student interaction. In addition, teachers become more confident and creative in developing interesting and relevant learning materials. The implications of these findings emphasize the importance of updating teaching methods as an effort to improve the quality of Islamic education in madrasahs. The recommendation for MTs Labanan Makmur is to continue supporting teacher professional development through training and the provision of facilities that support learning innovation. Thus, Islamic Religious Education learning will not only be a process of knowledge transfer, but also a vehicle for the comprehensive development of students' character and creativity